Modification of chitosan-methylcellulose composite films with meso-tetrakis(4-sulfonatophenyl)porphyrin - Synytsya, Alla; Grafová, Michaela; Slepicka, Petr; Gedeon, Ondrej; Synytsya, Andriy (Biomacromolecules, 2012)
Polysaccharide films containing chitosan, methylcellulose, and a mixture of these polysaccharides in various ratios were prepared and modified with meso-tetrakis(4-sulfonatophenyl)porphyrin in an aqueous medium at pH 7. The modified films were compared with the initial films using spectroscopic methods and microscopic imaging. Electronic (UV-vis absorption, electronic circular dichroism (ECD)) and vibrational (FTIR and Raman) spectra showed that the porphyrin macrocycles had a strong affinity toward chitosan and did not interact with the methylcellulose. The total porphyrin uptake depended on the chitosan: methylcellulose ratio and pure methylcellulose films did not retain porphyrin macrocycles. ECD measurements detected the presence of optically active porphyrin species bound to the films. SEM and AFM images confirmed that the porphyrin macrocycles caused structural changes on the film surface and within the film layer.
Keywords: Chitosan; Methylcellulose; absorpce; Circular Dichroism; methylcelulosa; Ramanova spektroskopie; Microscopy, Electron, Scanning; Drug Delivery Systems; molekulární struktura; Molecular Structure; cirkulární dichroismus; Biocompatible Materials; Porphyrins; spektroskopie infračervená s Fourierovou transformací; Spectroscopy, Fourier Transform Infrared; Spectrum Analysis, Raman; mikroskopie elektronová rastrovací; lékové transportní systémy; voda; Hydrogen-Ion Concentration; porfyriny; Water; biokompatibilní materiály; Absorption; koncentrace vodíkových iontů; chitosan